ANALISIS PENGELOLAAN KEUANGAN PRIBADI PADA MAHASISWA KELAS KARYAWAN DI UNIVERSITAS NUSA PUTRA - Sri Rima Yuningsih; Dara Selviana (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study aims to analyze personal financial management among employee class students at Nusa Putra University. The aspects studied include financial literacy, financial attitudes, financial behavior, and personal financial management. This study used a quantitative method with a descriptive approach. Data were obtained by distributing questionnaires using Google Forms through various social media platforms, namely WhatsApp and Instagram, with links shared with employee class students who have their own income and actively attend lectures. The number of respondents in this study was 56 students. The data analysis technique used was descriptive analysis, which aims to describe the financial management conditions of the respondents. The results showed that most employee class students have a fairly good awareness of the importance of personal financial management. This is evident in their savings habits, ability to prioritize expenses, financial planning, and use of savings as a source of funds for emergencies. Specifically, the results show that these students have high awareness in saving, prioritizing expenses, and preparing emergency funds, but remain weak in the consistency of financial recording. However, behind this, there are still several aspects that need to be improved, such as consistency in financial recording, spending control, and the formation of an adequate emergency fund. The results of this study indicate that although the level of financial awareness of students is quite good, the implementation of structured and sustainable financial management still needs to be strengthened to achieve a more stable and better financial condition.